Endophytic fungi: A treasure trove of novel anticancer compounds - Jignesh Prajapati; Dweipayan Goswami; Rakesh M. Rawal (Elsevier, 2021)
Cancer is a multifactorial disease with a convoluted genesis and progression. The emergence of multidrug resistance to presently be offered drug and relapse is by far, the most critical concern to tackle this deteriorating disease. Henceforth, there is undeniably an inflated necessity for safe, promising, and less harmful new anticancer drugs. Natural compounds from various sources like plants, animals, and microorganisms have occupied a center stage in drug discovery due to their tremendous chemical diversity and potential as therapeutic agents. Endophytic microbes are symbiotically associated with plants and have been proven to produce novel or analogues of host bioactive metabolites exhibiting a variety of biological activities including anticancer activity. This review emphasizes on structurally diverse unprecedented anticancer natural compounds that have been reported exclusively from endophytic fungi from 2016 to 2020. It covers chemical nature of metabolites, its fungal source associated with terrestrial, as well as marine plants and anticancer activity based on their cytotoxicity profile against various cancer cell lines. Many of these fungal metabolites with promising anticancer activity can be used as lead molecules for in silico experiments and deserve special attention from scientists for further in vitro and clinical research.